Penerapan Relaksasi Otot Progresif Pada Pasien Dengan Resiko Perilaku Kekerasan - Dyah Candaraningtyas; Sri Nyumirah (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
Abstract Background: The risk of violent behavior is an act that is capable of causing physical, emotional and sexual violence both to oneself and others. In controlling violent behavior can be done non-pharmacologically, namely with progressive muscle relaxation therapy. The benefits of progressive muscle relaxation are to provide a relaxed and calm feeling in the body. PKJN Marzoeki Mahdi Mental Hospital Boggor noted that patients with a risk of violent behavior in the Bratasena room during the last three months were 29.62%. Objective: To get the opportunity to provide nursing care and perform progressive muscle relaxation therapy in patients with the risk of violent behavior. Methods: The descriptive method is that the author is able to describe the patient with a form of nursing care starting from assessment to nursing evaluation using applied practice techniques supported by the real conditions of patients in the field. Results: It is hoped that the patient will be able to perform progressive muscle relaxation therapy 1x a day sequentially from head to toe with a duration of 10-15 minutes after application for 3 consecutive days, it is hoped that the patient will experience a decrease in signs of violent behavior, such as the tone of speech is not high, hands are not clenched, and the face is not red. Keywords: risk of violent behavior, progressive muscle relaxation therapy.